Stories to solve : folktales from around the world - Shannon, George; Sís, Peter (New York : Greenwillow Books, 1985)
Brief folktales in which there is a mystery or problem that the reader is invited to solve before the resolution is presented.
Bibliography: p. 54-55.
Keywords: Tales; Folklore; Literary recreations; Riddles